Spatial configuration matters when removing windfelled trees to manage bark beetle disturbances in Central European forest landscapes - Dobor, Laura; Hlásny, Tomáš; Rammer, Werner; Zimová, Soňa; Barka, Ivan; Seidl, Rupert (Journal of environmental management, 2020)
Windfelled Norway spruce (Picea abies) trees play a crucial role in triggering large-scale outbreaks of the European spruce bark beetle Ips typographus. Outbreak management therefore strives to remove windfelled trees to reduce the risk of outbreaks, a measure referred to as sanitation logging (SL). Although this practice has been traditionally applied, its efficiency in preventing outbreaks remains poorly understood. We used the landscape simulation model iLand to investigate the effects of different spatial configurations and intensities of SL of windfelled trees on the subsequent disturbance by bark beetles. We studied differences between SL applied evenly across the landscape, focused on the vicinity of roads (scenario of limited logging resources) and concentrated in a contiguous block (scenario of spatially diversified management objectives). We focused on a 16 050 ha forest landscape in Central Europe. The removal of >80% of all windfelled trees is required to substantially reduce bark beetle disturbances. Focusing SL on the vicinity of roads created a "fire break effect" on bark beetle spread, and was moderately efficient in reducing landscape-scale bark beetle disturbance. Block treatments substantially reduced outbreaks in treated areas. Leaving parts of the landscape untreated (e.g., conservation areas) had no significant amplifying effect on outbreaks in managed areas. Climate change increased bark beetle disturbances and reduced the effect of SL. Our results suggest that past outbreak management methods will not be sufficient to counteract climate-mediated increases in bark beetle disturbance.
Keywords: brouci; Evropa; Europe; Norsko; Animals; Forests; Coleoptera; Wind-bark beetle interactions; kůra rostlin; Forest landscape; Climate change; Sanitation logging; zvířata; lesy; Norway; Process-based ecosystem modelling; stromy; Plant Bark; Trees